Faith, values, and metaphysical positionality in qualitative research. Issue 1 (20th September 2021) - Johnsen, Sarah; Fitzpatrick, Suzanne
Abstract: Positionality has long been a preoccupation for qualitative researchers within and beyond geography. Reflexive assessments of positionality typically examine the ways in which a researcher's sociodemographic identifiers such as gender, age, ethnicity, dis/ability, sexuality, and/or the intersections between these affect research encounters, processes, and outcomes. Religion rarely features in such interrogations, and then usually only in relation to participants' ethnic or racial affiliations. Drawing on experiences conducting a study exploring the role of faith‐based organisations in welfare provision for homeless people in the UK, this paper focuses on the related (but not synonymous) issue of metaphysical stance, that is, belief or non‐belief in the existence of God(s). It argues that metaphysical stance should be regarded as a sui generis aspect of positionality, which fits into none of the identity categories typically considered but is deserving of separate analysis with respect to its ethical and practical implications. Further to this, it contends that extreme diplomacy and discretion are required when exploring issues as inherently value‐laden as the moral frameworks underpinning welfare approaches. This is especially true when participants' views divide in part along theist/atheist lines, such that religious and policy "literacy" are valuable attributes for researchers negotiating these sensitive terrains in the field. Abstract : Building on and critiquing existing scholarship on researcher reflexivity within and beyond geography, this paper argues that metaphysical stance should be regarded as a sui generis aspect of positionality that fits into none of the sociodemographic identity categories typically considered but is deserving of separate analysis with respect to its ethical and practical implications.